Evolving imaging methods of prostate cancer and the emergence of magnetic resonance imaging guided ablation techniques - Anttinen, Mikael; Blanco Sequeiros, Roberto; Boström, Peter J.; Taimen, Pekka (Frontiers in Oncology, 2022)
Established therapies for prostate cancer (PCa), surgery and radiotherapy, treat the entire gland regardless of the location of the cancerous lesion within the prostate. Although effective, these methods include a significant risk of worsening genitourinary outcomes. Targeted image-guided cancer therapy has gained acceptance through improved PCa detection, localization, and characterization by magnetic resonance imaging (MRI). Minimally-invasive ablative techniques aim to achieve comparable oncological outcomes to radical treatment while preserving genitourinary function. Transurethral ultrasound ablation (TULSA) and next-generation transrectal high-intensity focused ultrasound (HIFU) utilize MRI guidance to thermally ablate prostate tissue under real-time MRI monitoring and active temperature feedback control. Previous trials performed by our group and others, including a large multicenter study in men with localized favorable-risk disease, have demonstrated that TULSA provides effective prostate ablation with a favorable safety profile and low impact on quality of life. Recently, MRI-guided HIFU focal therapy was also shown as a safe and effective treatment of intermediate-risk PCa. Here we review the current literature on ablative techniques in the treatment of localized PCa with a focus on TULSA and HIFU methods.